Gambaran Status Kebersihan Rongga Mulut dan Status Gingiva Pasien RSGM Universitas Jember Oktober-November Tahun 2015 (The Description of Oral Hygiene Status and Gingival Status of Patients in Dental Hospital of Jember University on October-November 2015) - Cici Widya Anggraini; Melok Aris Wahyukundari; Peni Pujiastuti (Pustaka Kesehatan, 2016)
Background : Oral hygiene is very important to be kept for aestetic, phonetic, mastication function and health. There is a relationship between oral hygiene and gingival desease. Poor oral hygiene will increase the severity of gingival disease. However, some people still consider that oral hygiene issue is not something important. Purpose : To find out the status of oral hygiene and gingival status of patients in Dental Hospital of Jember University and reviewed by age, gender and education. Metode : This study was a descriptive study with cross sectional approach. The samples were all new patients of Dental Hospital of Jember University on October-November 2015. The oral hygiene status was assessed by Oral Hygiene Index-Simplified (OHI-S) and gingival status was assessed by Gingival Index (GI). Result : There were 35,84% of sample had a good oral hygiene, 54,87% had a medium oral hygiene and 9,29% had a poor oral hygiene. There were 7,08% of sample had a normal gingival, 58,85% had a light gingival inflamation, 33,63% had a moderate gingival inflamation, and 0,44% had a severe gingival inflamation.Keywords : Gingivitis, GI, OHI-S, Oral hygiene.